Manajemen Fundraising Zakat Profesi di Kalangan Aparatur Sipil Negara untuk Meningkatkan Perolehan Zakat Profesi pada UPZ Unit Koordinator Wilayah Kecamatan Panggul - Kustia Rahayu; Ahmad Supriyadi (ZAWA: Management of Zakat and Waqf Journal, 2022)
Management was defined as the process of organizing, managing, seeking, leading and utilizing resources effectively to achieve goals. This research was focused on the implementation of profession zakat fundraising management among State Civil Servants at UPZ Regional Coordinator Unit for Education in Panggul district. The management functions studied were in the form of planning, implementating and supervising profession zakat fundraising. The implementation of profession zakat fundraising management at UPZ Regional Coordinator Unit Panggul district has been good. The research method used is a qualitative descriptive approach with the type of field research.